Enhancing Employee Productivity in UAE’s Retail Sector: Integrating Maslow’s Hierarchy and Industry 4.0 - Badubhai, Fayaz Ahamed (Digital Repository of Theses, 2024)
The purpose of this research is to determine how Industry 4.0 and Maslow's hierarchy of needs can be integrated to improve employee efficiency in the UAE retail sector. In the UAE retail context, this research evaluated many aspects of employee contentment in relation to digital transformation. It investigated the association between staff satisfaction and its many variables, including Industry 4.0 technology and innovation as well as psychological, social, esteem, security, and self-actualisation demands, using cross-tabulations and chi-square analyses. The data was collected using a questionnaire survey that focuses on enhancing employee productivity in the retail sector of the UAE by integrating Maslow's Hierarchy and Industry 4.0. The main conclusions demonstrated that individuals’ accessibility to resources and assistance to create innovations is moderately coordinated. Regarding gaining constructive criticism, having access to technology that would help them be more productive, comprehending and adjusting to technological advancements, and the efficacy of the training, they exhibit neutrality or a minor disagreement. Based on statistical analysis, the result obtained from the Chi-square test indicated that there is no significant correlation between the variables and employee satisfaction. This implies that there is no evidence pointing to a connection between worker productivity and their satisfaction with the present digital transition. However, it appears from the literature that embracing Industry 4.0 could increase productivity and competitiveness. Literature even draws attention to the significance of innovation in retail operations, the necessity of upskilling and training in order to adapt to digital transformation, and the significance of addressing various requirements in accordance with Maslow's hierarchy of needs in order to be most effective and fulfilled. Lastly, research on innovation and digital advancement frequently highlights the significant potential advantages that both may provide. The outcomes of the questionnaire are presented in this study, which shows that neither innovation nor digital transformation is statistically substantially associated with higher employee satisfaction in the present organisational context. Keywords: Employee Productivity, UAE's Retail Sector, Retail Industry, Maslow's Hierarchy, Industry 4.0.